Green building and leed core concepts (U.S. Green Building Council, 2011)
The second edition of this outstanding reference provides a solid foundation for the study of green building and LEED (Leadership in Energy and Environmental Design). It explains many of the important tenets of green building while providing strategies for implementation and specific case studies designed to broaden your knowledge of green building.